Mothers and fathers with young children: Paid employment, caring and wellbeing - Alexander, M; Strazdins, L; Baxter, Jennifer; Bittman, M; Gray, M (My University, 2007)
The paper examines how the use of child care, the time parents spend with children, and parental well being relate to parental employment. The analysis is based on Wave 1 of the Longitudinal Survey of Australian Children (LSAC) confidentialised unit record file. Four themes are addressed in the report: the labour force status and job characteristics of parents with young children; patterns of use of child care and how they vary according to parental employment status; the impact of parental employment on parenting and time spent with children; the relationship between parental employment status and the wellbeing of parents.
Social Policy Research Papers
Keywords: Families -- Work/family balance; Families; Families and relationships; Families; Work/family balance; Families and relationships